Membedah Kasus Kopi Sianida Jessica Wongso dengan Ajaran Kausalitas - Siregar, Vivi Maria Fransiska; Purnomo, Hadi (AHKAM, 2023)
The case of "Jessica Wongso Cyanide Coffee" is in the public spotlight because of the controversy involving the death of Wayan Mirna Salihin after drinking coffee at a café in Jakarta. In this study, we dissected the case with a doctrinal approach to causality, focusing on identifying the cause-and-effect relationship between Jessica Wongso's actions and the criminal outcomes that occurred. The in-depth analysis covers various aspects, including the identification of causal actions through forensic and toxicological evidence, Jessica's role in events, as well as the relevance of the principle of causality in the context of criminal law. This study delves into the details of criminal legal proceedings, outlines the role of toxicological evidence in confirming cyanide content in victims' bodies, and discusses the complexity of causality in the context of criminal acts. Taking a multidisciplinary approach, this article discusses the legal and ethical implications surrounding Jessica Wongso's liability, as well as considering the causal elements that might influence the court's decision. In conclusion, this research contributes to an in-depth understanding of how the concept of causality is applied in controversial and complex legal cases such as "Jessica Wongso's Coffee Cyanide."